A new Australian species of invasive psyllid, Acizzia convector Burckhardt & Taylor, sp. nov. (Psylloidea: Psyllidae) associated with Acacia auriculiformis and A. mangium (Fabaceae) - Taylor, Gary S.; Halbert, Susan E.; Tripathy, Ashirwad; Burckhardt, Daniel (Zootaxa, 2023)
Acizzia convector Burckhardt & Taylor, sp. nov., a psyllid originating from Australia, is described from material from Australia (NT), South and Southeast Asia (Brunei, Cambodia, India, Laos, Malaysia [Sabah], Singapore and Thailand) and North America (USA [Florida from six counties]). The new species is diagnosed and illustrated, and a key is provided to identify the adults of Acizzia species adventive in the New World. The new species develops on Acacia auriculiformis and A. mangium (Fabaceae), two mimosoids planted and widely naturalised throughout the tropics. While the presence of A. convector sp. nov. in Florida is probably recent (earliest record from October 2014), it occurs in Southeast Asia at least since the 1980s. The wide distribution of the host plants in tropical Africa and South America would allow the psyllids also to occur there.